Cervical Approach for Retrosternal Struma: A Case Report - Tandililing, Sherly; Sipayung, Edwin Z. (Medical Scope Journal, 2025)
Abstract: Retrosternal struma is the inclusion of the thyroid gland into the thoracic cavity. Combined access with a neck incision and chest incision or only a neck incision to free the tumor from the chest cavity and avoid damage to surrounding tissues, makes treatment of substernal struma a challenge both preoperatively and during surgery. Systematic technique minimizes the need for sternotomy, even in patients with significant intra thoracic components, and keeps severe complication rates at levels comparable to those of conventional thyroidectomy. We reported a 46-year-old woman complaining of lumps on the right and left neck for six years. The masses were found on the right side of the neck (10x6cm) and on the left side of the neck (4x3cm), which were hard consistency, well-defined, immobile, skin-colored, painless, and moving when swallowing. CT-scan showed a solid mass struma that had entered the superior thoracic aperture. Total thyroidectomy was performed through cervical approach with a good outcome. In conclusion, total thyroidectomy through a cervical approach is able to remove the entire thyroid gland tissue extending to the retrosternal region with a good outcome without performing a sternotomy. Keywords: retrosternal struma; thyroidectomy; cervical approach